Assessing care: progress towards the measurement of selected childcare and feeding practices, and implications for programs - Arimond, Mary; Ruel, Marie T. (International Food Policy Research Institute, 2001)
The objective of this report is to summarize progress towards measurement of selected childcare and feeding practices, and to discuss the feasibility and usefulness of these measurements in research and program contexts. This is the third in a series of reports documenting insights regarding care and measurement of care gained from the Accra Urban Food and Nutrition Study (AUFNS). This last report complements the previous two by providing an extensive review of the published literature on experience with the measurement of selected dimensions of care.